Reducing Tourniquet Pressures in Hand Surgery: Are Lower Pressures as Effective? - Azad, Ali; Sager, Brian; Gupta, Salil; Ayalon, Omri; Paksima, Nader (Journal of Wrist Surgery, 2022)
Background Pneumatic tourniquets are widely used in hand surgery. Elevated pressures can be associated with complications, and thus, guidelines based on patient-specific tourniquet pressures have been recommended. The primary aim of this study was to determine whether lower tourniquet values based on systolic blood pressure (SBP) could be effectively applied in upper extremity surgery.Methods A prospective case series of 107 consecutive patients undergoing upper extremity surgery with use of a pneumatic tourniquet was performed. Tourniquet pressure used was based on the patient's SBP. The tourniquet was inflated based on our predetermined guidelines: 60 mm Hg was added for SBP < 130 mm Hg, 80 mm Hg for SBP between 131 and 190 mm Hg, and 100 mm Hg for SBP > 191 mm Hg. The outcome measures included intraoperative tourniquet adjustment, surgeon-rated quality of bloodless operative field and complications.Results The mean tourniquet pressure was 183 ± 26 mm Hg with a mean tourniquet time of 34 minutes (range: 2–120 minutes). There were no instances of intraoperative tourniquet adjustment. The surgeon-rated quality of bloodless operative field was excellent in all patients. No complications were associated with the use of a tourniquet.Conclusion Tourniquet inflation pressure based on SBP is an effective method to provide a bloodless surgical field in upper extremity surgery at significantly lower inflation pressures than are the current standards.
Keywords: upper extremity surgery; hand surgery; tourniquet; systolic blood pressure; bloodless surgical field